Developing cognitive bots using the IBM Watson engine : practical, hands-on guide to developing complex cognitive bots using the IBM Watson Platform /: practical, hands-on guide to developing complex cognitive bots using the IBM Watson Platform. (©2020) - Unknown
No abstract available